(untitled) - Abbas, Abul K. (Philadelphia, P.A., 2005)
The meticulously revised and updated New Edition of this highly acclaimed text continues to provide a concise and straightforward approach to the subject. It focuses on the experimental observations that underlie the science of immunology at the molecular, cellular, and whole organism level-and explores the conclusions that can be drawn from those observations.
Keywords: Cellular immunity,Molecular immunology